Notes on the Economic Evaluation of Transport Projects - Mackie, Peter (World Bank, Washington, DC, 2012)
Experience has shown that money compensation payments to individual citizens are ineffective when used alone as a means to achieve the Bank's aims and World Bank for evidence on the Bank's experience]. Instead, the Bank's advice is that compensation payments should be a part of a wider, coordinated package of development assistance. It is not the purpose of this Note to describe how such a package should be developed, or indeed how the package as a whole should be evaluated. Rather, the question addressed in this Note is the narrower one: How should money compensation payments be evaluated? Section 2 begins by asking what costs the payments are intended to compensate for, and on what basis the value of compensation should be estimated. Section 3 continues to consider how institutional arrangements affect the way compensation payments are designed and channeled in practice. Section 4 turns to the benefits of resettlement compensation and Section 5 brings these strands together to consider how compensation payments should be evaluated within the economic evaluation of World Bank transport projects.